Drug-Induced Liver Injury in Children - Matniyozova Zaynabjon Toxtaboyevna (Journal of Science in Medicine and Life, 2025)
The most common and dangerous side effect of drug therapy is hepatotoxicity. The liver, as the primary organ where drugs are metabolized, is particularly susceptible to the damaging effects of medications and toxins. Drug-induced liver injury (DILI) is the most frequent reason for the discontinuation of new drug development. In developed countries, medication use is the leading cause of liver failure and the most common indication for liver transplantation.